2020
DOI: 10.1259/bjr.20190958
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic radiotherapy for inoperable gastric cancer: a pilot study

Abstract: Objective: Standard treatment for progressive gastric cancer with bleeding includes hemostatic radiotherapy (RT); however, the only prospective study using a fixed dose with fractions during hemostatic RT did not introduce re-irradiation. Therefore, we determined the utility of RT including re-irradiation for gastric cancer. Methods: In this study, 31 patients with gastric cancer and bleeding were treated with an initial dose of 20 Gy/5 fractions for the whole stomach and a salvage dose of 15 Gy/5 fractions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…The hemostatic effect of radiotherapy on gastric cancer has been confirmed previously by our group and Tey et al in prospective trials [ 1 , 2 ]. Our study reported the effectiveness of hemostatic irradiation and the possibility of re-irradiation [ 3 , 4 ], and Tey et al reported on quality of life.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…The hemostatic effect of radiotherapy on gastric cancer has been confirmed previously by our group and Tey et al in prospective trials [ 1 , 2 ]. Our study reported the effectiveness of hemostatic irradiation and the possibility of re-irradiation [ 3 , 4 ], and Tey et al reported on quality of life.…”
Section: Introductionsupporting
confidence: 71%
“…Subsequently, 15 Gy/5 fractions treatment was administered to patients who had rebleeding and wished to be re-irradiated. Hemostasis was observed in 6/6 (100%) [1] . On the other hand, according to the report by Tey et al , the same therapeutic degree of effect was observed in 40/50 (80%) of their patients [2] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study reveals that the adrenal glands may be able to regulate the radiation dose to the stomach and left kidney by changing the shape (size) of the stomach. MRI-Linac can reduce the target's intra-and intervariance but not the contents of the stomach [17]. Therefore, we believe that MR-Linac will become widespread, but also that such a method of arti cially changing the shape and position of organs is necessary.…”
Section: Future Outlook (Compared With Mr-linac)mentioning
confidence: 99%